Penguatan Pendidikan Agama Islam Pada Madrasah Aliyah Bertaraf Internasional Di Insan Cendekia Serpong - Samsirin Samsirin; Rizki Putri Utami; Aghnasalisa Inas; Herdina Fatma; Sal Sakhiba Albira (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2023)
The purpose of the researchers was to find out how to strengthen the development of the Islamic Education curriculum in this school which is considered to have good advantages. The method used in this study is a qualitative approach. With this method, information can be obtained by researchers through websites, journals, school info, and others. In data analysis, researchers used qualitative descriptive techniques. The initial conclusion states that the existing educational development at the Insan Cendikia Madrasah, which incidentally is an international standard school, turns out to have strong reinforcement through many programs, activities, strategies, curricula, evaluations, and so on, which were deliberately made by its founders. Meanwhile, in improving the quality of education, this madrasa integrates school programs with boarding programs, builds school culture and networks, and improves human resources and facilities.